Exploring the Impact of Systemic Inflammatory Regulators on Rosacea Risk: A Bidirectional Mendelian Randomization Analysis - Xue Q; Pan JP; Qian D; Ji J; Fei LY; Yao S; Tan X; Fan WG (Clinical, Cosmetic and Investigational Dermatology)
Qiao Xue,1 Jian Peng Pan,2 Da Qian,3 Jie Ji,4 Lai Yi Fei,1 Sheng Yao,1 Xing Tan,1 Wen Ge Fan1 1Department of Dermatology, Changshu No. 1 People’s Hospital, Changshu Hospital Affiliated to Soochow University, Changshu, Jiangsu, 215500, People’s Republic of China; 2Department of Hand Surgery, Changshu No. 2 People’s Hospital, The Affiliated Changshu Hospital of Nantong University, Changshu, Jiangsu, 215500, People’s Republic of China; 3Department of Burn and Plastic Surgery-Hand Surgery, Changshu No. 1 People’s Hospital, Changshu Hospital Affiliated to Soochow University, Changshu, Jiangsu, 215500, People’s Republic of China; 4Department of Dermatology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, 210000, People’s Republic of ChinaCorrespondence: Qiao Xue, Department of Dermatology, Changshu Hospital Affiliated to Soochow University, Changshu No. 1 People’s Hospital, No. 1 Shuyuan Street, Yushan Town, Changshu, Jiangsu, 215500, People’s Republic of China, Tel +86-13913657476, Email ahjk157@126.com Jian Peng Pan, Department of Hand Surgery, The Affiliated Changshu Hospital of Nantong University, Changshu No. 2 People’s Hospital, 68 South Haiyu Road, Yushan Town, Changshu, Jiangsu, 215500, People’s Republic of China, Tel +86-13814964481, Email 574161036@qq.comObjective: Rosacea is a common chronic inflammatory disorder primarily affecting the face. While inflammatory factors are known to play a pivotal role in its pathogenesis, their causal relationship with rosacea remains unclear. This study employed a two-sample bidirectional Mendelian randomization (MR) analysis to investigate the causal links between systemic inflammatory regulators and rosacea.Methods: Data on 41 cytokines and growth factors were analyzed from a genome-wide association study (GWAS) meta-analysis involving 8293 individuals and genetic data from the FinnGen database, comprising 1195 rosacea cases and 211,139 controls. The principal inverse variance weighting (IVW) method was used to assess causal relationships, with sensitivity analyses, including heterogeneity and horizontal pleiotropy assessments, conducted to ensure result robustness.Results: MR analysis revealed that decreased expression of Stem Cell Factor (SCF), Macrophage Inflammatory Protein-1β (MIP-1β), and Monocyte Chemotactic Protein-1 (MCP-1) was associated with increased rosacea risk (OR = 1.54, 95% CI = 1.05– 2.26, p = 0.026). Conversely, elevated expression levels of Stromal Cell-Derived Factor-1α (SDF-1α) and Hepatocyte Growth Factor (HGF) were linked to higher rosacea risk (OR = 1.61, 95% CI = 1.12– 2.31, p = 0.009). Reverse MR analyses showed no significant impact of rosacea on systemic inflammatory regulator expression.Conclusion: This study identified five inflammatory factors—SCF, SDF-1α, MCP-1, HGF, and MIP-1β—as having causal relationships with rosacea pathogenesis. Further research is required to elucidate their mechanistic roles in disease development.Keywords: rosacea, inflammation, risk, Mendelian randomization, MR, cytokine